2004
DOI: 10.1051/0004-6361:20035909
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the luminosity functions in the FORS Deep Field from low to high redshift

Abstract: Abstract. We use the very deep and homogeneous I-band selected dataset of the FORS Deep Field (FDF) to trace the evolution of the luminosity function over the redshift range 0.5 < z < 5.0. We show that the FDF I-band selection down to I AB = 26.8 misses of the order of 10% of the galaxies that would be detected in a K-band selected survey with magnitude limit K AB = 26.3 (like FIRES). Photometric redshifts for 5558 galaxies are estimated based on the photometry in 9 filters (U, B, Gunn g, R, I, SDSS z, J, K an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
252
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(282 citation statements)
references
References 113 publications
(243 reference statements)
29
252
1
Order By: Relevance
“…One sample is selected in luminosity, M B −20 (∼M * B at z ∼ 0; Faber et al 2007), which comprises 1122 sources. The value of M * B is 1 mag brighter at z ∼ 1 than locally (Gabasch et al 2004;Ilbert et al 2005;Faber et al 2007), evolution that reflects the descent in the star formation rate density of the universe since z ∼ 1 (e.g., Hopkins & Beacom 2006). Hence, if we assume a constant M B 7 http://www.stsci.edu/science/goods/ 8 http://archive.stsci.edu/prepds/goods/ 9 http://guaix.fis.ucm.es/∼pgperez/Proyectos/ucmcsdatabase.en.html cut, we select different areas of the luminosity function at each redshift, biasing our results.…”
Section: Galaxy Samplesmentioning
confidence: 78%
“…One sample is selected in luminosity, M B −20 (∼M * B at z ∼ 0; Faber et al 2007), which comprises 1122 sources. The value of M * B is 1 mag brighter at z ∼ 1 than locally (Gabasch et al 2004;Ilbert et al 2005;Faber et al 2007), evolution that reflects the descent in the star formation rate density of the universe since z ∼ 1 (e.g., Hopkins & Beacom 2006). Hence, if we assume a constant M B 7 http://www.stsci.edu/science/goods/ 8 http://archive.stsci.edu/prepds/goods/ 9 http://guaix.fis.ucm.es/∼pgperez/Proyectos/ucmcsdatabase.en.html cut, we select different areas of the luminosity function at each redshift, biasing our results.…”
Section: Galaxy Samplesmentioning
confidence: 78%
“…Below this, VVDS claims to see a steepening in faint-end slope from $ À1:2 at z ¼ 0:05 to $ À1:5 at z ¼ 1. Neither DEEP2 nor COMBO-17 goes deep enough to test this, but, as noted in x 1, Gabasch et al (2004;FDF) go 2.5 mag fainter and do not see it, getting ¼ À1:25 at all redshifts. Relative to the local Schechter function, the All data brighten back in time (M Ã B ) but stay roughly constant in number density ( Ã ).…”
Section: The Deep and Combo-17 Luminosity Functionsmentioning
confidence: 93%
“…In spite of lower precision, photometric redshifts yield a larger number of redshifts per unit telescope time and enable distances to be measured for galaxies that are too faint for spectroscopy. This approach has been pursued using both spacebased (e.g., Takeuchi et al 2000;Poli et al 2001;Bolzonella et al 2002) and ground-based data (e.g., Fried et al 2001;Drory et al 2003;Wolf et al 2003, hereafter W03;Chen et al 2003;Gabasch et al 2004). Of the photometric redshift surveys, the ones most comparable to the present work are and the FORS Deep Field (FDF; Gabasch et al 2004).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…No other nearby objects are found at the 3σ significance level (corresponding to 0.03 L * ). At z = 2 a luminous L * galaxy has an absolute magnitude of U * AB = −21.9 mag (Gabasch et al 2004), and an observed magnitude of U AB = 24.0 mag in the adopted cosmology. The numbered objects in Fig.…”
Section: Nearby Galaxies and Coloursmentioning
confidence: 98%